Clinical Impact of Chronic Aortic Regurgitation in Asymptomatic Patients with Native Aortic Valve Stenosis. Issue 5 (3rd September 2018) - Sorajja, Paul; Nelson, Patrick; Garberich, Ross; Bradley, Steven M.; Athappan, Ganesh; Bae, Richard; Harris, Kevin; Lesser, John; Tindell, Lisa; Farivar, R. Saeid; Goessl, Mario
ABSTRACT: Background : The pathologic processes of aortic regurgitation (AR) and aortic stenosis (AS) can affect the rate of progression to symptoms differently, and insight into the management of mixed aortic disease is needed. We examined the impact of concomitant AR in asymptomatic patients with AS. Methods : We examined 308 asymptomatic patients (mean age, 76 ± 13 yrs; 62% men) with moderate or severe AS seen at our institution, and compared outcomes according to the presence of AR. Results : Over 5.5 [2.7, 6.7] years, the presence of AR significantly impacted outcomes in patients with moderate, but not severe AS. For patients with moderate AS, the 4-year survival free of death, cardiac symptoms, or aortic valve replacement (AVR) was 47.1%, 30.9%, and 29.0% for none, mild, and moderate/severe AR, respectively ( p = 0.02), and this relation remained significant after adjustment for morbidities in multivariate analyses (HR, 2.21 [1.31–3.74] for moderate/severe AR, p = 0.003). The median time to symptom onset was shorter with worse AR in patients with moderate AS (34.8, 32.1, and 24.0 months for none, mild, and moderate/severe AR, respectively; p = 0.08). There was no relation of concomitant AR to increased risk of death, symptoms, and AVR in patients with severe AS. Conclusion : The presence of AR increases the risk of need for AVR, but not death, in patients with moderate AS. Asymptomatic patients with severe AS have comparable long-term outcomes regardless of AR severity. These data have implications for clinical follow up and timing of surgery.